Analysis of Student Learning Difficulties in Plants Physiology Online Lectures During Pandemic of COVID–19 - Ranti An Nisaa; Devi Anugrah (Jurnal Penelitian Pendidikan IPA, 2024)
The COVID-19 pandemic made higher education institutes support online education. Searching for the learning difficulties of students who have gone through lectures online needs to be done as anticipation and looking for solutions in the next lecture. This quantitative descriptive research was conducted in biology education study programs that have studied Plant Physiology in the 2020-2021 academic years. 56 respondents were given a questionnaire related to their difficulties during the online lectures. Learning difficulties in the external aspect were the slow internet network (58.90%) and the internal aspect was very difficult to focus on listening to online lectures if the room where the lecture was messy (58.90%). Physical and physical health profile, easy to get sore and sleepy during the course (57.10%). On the profile of academic learning, students find it more difficult to find textbooks during online lectures than during offline lectures (69.60%). The characteristics of the courses that affected the mastery of the material were the presence of many illustrations of physiological processes (30.40%) and complex concepts (30.40%). Lecturers and students work together to overcome these difficulties so as not to disrupt the overall course of lectures so that online lectures continue well.